2007
DOI: 10.1371/journal.ppat.0030119
|View full text |Cite|
|
Sign up to set email alerts
|

Genome Dynamics of Campylobacter jejuni in Response to Bacteriophage Predation

Abstract: Campylobacter jejuni is a leading cause of food-borne illness. Although a natural reservoir of the pathogen is domestic poultry, the degree of genomic diversity exhibited by the species limits the application of epidemiological methods to trace specific infection sources. Bacteriophage predation is a common burden placed upon C. jejuni populations in the avian gut, and we show that amongst C. jejuni that survive bacteriophage predation in broiler chickens are bacteriophage-resistant types that display clear ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
148
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 53 publications
7
148
1
Order By: Relevance
“…One of these, named 11168R, was further characterized. Previously, loss of motility and genomic rearrangements have been associated with phage resistance development in C. jejuni (8,46). Phenotypic characterization showed that neither the motility nor the ability to autoagglutinate had changed in 11168R ( Table 2), indicating that the flagella and components important for cell-to-cell interactions were unaffected by the bacteriophage F336 resistance phenotype.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One of these, named 11168R, was further characterized. Previously, loss of motility and genomic rearrangements have been associated with phage resistance development in C. jejuni (8,46). Phenotypic characterization showed that neither the motility nor the ability to autoagglutinate had changed in 11168R ( Table 2), indicating that the flagella and components important for cell-to-cell interactions were unaffected by the bacteriophage F336 resistance phenotype.…”
Section: Resultsmentioning
confidence: 98%
“…For Campylobacter, only little is known about how phages recognize this bacterium, and to date no phage receptors have been identified. However, previous studies imply that both the capsule and the flagella of Campylobacter could be involved in the recognition by phages (8,46). Thus, the initial phage-host interaction is highly understudied for this bacterium.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…118 This phenomenon was observed for phage resistant derivatives of Campylobacter jejuni which were unable to efficiently colonize the broiler chicken intestine. 119 Recent studies have demonstrated that phage resistant mutants may have functional properties that differ from those of the parental strain. Phage resistant derivatives of Lactobacillus delbreuckii strains demonstrated either a preserved or enhanced ability to activate the small intestinal immune response of BALB/C mice who received pure preparations of phage sensitive or phage resistant cultures over 7 consecutive days.…”
Section: Perspectivementioning
confidence: 99%
“…Nevertheless some of the above mentioned studies found that phage resistance can be associated with a reduced colonization potential in the chicken intestine, suggesting that there is a fitness cost to phage resistance in which phage-resistant Campylobacter revert to a sensitive phenotype when re-colonizing the chicken intestine in the absence of phage predation. It was also suggested that genomic instability of C. jejuni in the avian gut can be seen as a mechanism to temporarily survive phage predation and later competition for resources (Carvalho et al, 2010a;Loc Carrillo et al, 2005;Scott et al, 2007a;Scott et al, 2007b). Conversely, recent studies by reported that Campylobacter strains resistant to phage infection were recovered from phage-treated chickens at a frequency of 13% and that these resistant phenotypes did not exhibit a reduced ability to colonize the chicken guts and did not revert to sensitive types (Carvalho et al, 2010a).…”
Section: Campylobactermentioning
confidence: 99%